2022
DOI: 10.1186/s40798-022-00527-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acute Resistance Exercise on Executive Function: A Systematic Review of the Moderating Role of Intensity and Executive Function Domain

Abstract: Background Research has demonstrated that there is a beneficial effect of acute exercise on cognitive function; however, the moderators of the acute resistance exercise (RE) effect on executive function (EF) are underestimated. This systematic review aims to clarify the effects of acute RE on EF by examining the moderating effect of exercise intensity (light, moderate, and vigorous) and EF domains (inhibitory control, working memory, and cognitive flexibility), as well as their interactions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 85 publications
1
4
0
Order By: Relevance
“…This lack of significant differences between high-and low-intensity exercise with regard to cognitive outcomes may be explained by the individual conditions of the participants, as well as the type and intensity of the PA. Evidence from a systematic review [48] evaluating the moderating effects of exercise intensity in healthy subjects aged 18 years or older indicated that moderate acute resistance exercise consistently shows beneficial effects on inhibitory control, while light or vigorous intensity resistance exercise yielded benefits in about 50% of cases, aligning with the results found in the present systematic review.…”
Section: Discussionsupporting
confidence: 86%
“…This lack of significant differences between high-and low-intensity exercise with regard to cognitive outcomes may be explained by the individual conditions of the participants, as well as the type and intensity of the PA. Evidence from a systematic review [48] evaluating the moderating effects of exercise intensity in healthy subjects aged 18 years or older indicated that moderate acute resistance exercise consistently shows beneficial effects on inhibitory control, while light or vigorous intensity resistance exercise yielded benefits in about 50% of cases, aligning with the results found in the present systematic review.…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, whether different modes of CE, which combine traditional sequential movement resistance exercise, are beneficial for exercise-induced cognitive function remains to be clarified. Furthermore, acute RE has garnered recognition as a significant and promising exercise modality within the realm of exercise and cognitive function ( Huang et al, 2022 ; Wilke et al, 2019 ); however, there are relatively few studies investigating the effects of RE on cognitive function compared to study targeted on AE ( Chow et al, 2021 ). Therefore, the present study specifically incorporates RE condition for comparison, aiming to address the limitations of previous studies in this area.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a meta-analytic review of randomized controlled trials showed notable enhancements in executive functions, as assessed through standardized cognitive assessments, after a 12-week aerobic exercise program [120]. Likewise, resistance training programs have been found to have beneficial impacts on cognitive flexibility and processing speed, leading to faster reaction times and enhanced task-switching abilities in individuals who participate in resistance exercises that focus on major muscle groups [121]. Additionally, Tai Chi and yoga have been associated with improvements in overall cognitive function, especially in areas like verbal memory, visuospatial skills, and processing speed.…”
Section: Importance Of Tailored Interventions Targeting Specific Outc...mentioning
confidence: 99%